J9 Probing huntington's disease phenocopy syndromes with next-generation sequencing. (13th September 2016) - Koriath, Carolin; Adamson, Gary; Druyeh, Ronald; Kenny, Janna; Collinge, John; Wild, Edward; Houlden, Henry; Gaskin, Mark; Mead, Simon; Tabrizi, Sarah
Abstract : Background and aims: Huntington's disease (HD) is an autosomal-dominant condition and defined by a triad of movement, cognitive, and psychiatric symptoms. However, some patients in whom HD is suspected do not carry the CAG expansion in the Huntingtin gene ( HTT ). These cases, with symptoms on the HD spectrum, but without the HTT expansion, are called HD phenocopy syndromes. Their most frequent known cause has recently been identified as C9orf72, but recessive conditions can also mimic HD. Next generation sequencing technologies (NGS) facilitate the simultaneously screening of genes linked to other neurodegenerative conditions. Methods: We applied a validated 17-gene NGS dementia panel ( PRNP, PSEN1, PSEN2, APP, GRN, MAPT, TREM2, CHMP2B, CSF1R, FUS, ITM2B, NOTCH3, SERPINI1, SQSTM1, TARDBP, TYROBP and VCP ) combined with PCR-based assessments of the C9orf72 and PRNP expansions to the UCL HD phenocopy cohort (n = 444). We classified mutations by likelihood of pathogenicity and compared with clinical data, including HD-likeness and family history. Results: In the cohort, 7.2% of all patients displayed the complete triad of symptoms, and for 46.9% of these a relevant family history was reported. A further 32.7% presented with 2/3 of the triad, 20.3% of these had a relevant family history. Overall, a relevant family history was reported for 24% of patients. In the 409 cases processed so far, yet to be tested for the C9orf72 and PRNP expansions, 4.5% of patients were found to carry a (likely) deleterious variant, a further 4.1% carried a potentially deleterious variant and 7.9% carried a higher-risk allele. Conclusions: A custom panel provides affordable high quality sequencing. These panels can now help identify mutations in genes not previously linked to HD phenocopies, and reduce the number of cases where even with a strong family history no genetic mutation is found. This ongoing work will help to provide answers to patients and families, who present with an HD syndrome without the diagnostic certainty of the HTT expansion.